Glomerulonephritis and Interstitial Nephritis Originating from Vasculitis of the Interlobular Arteries of the Kidney in a Patient with Eosinophilic Granulomatosis with Polyangiitis - Takashi Nawata; Masaki Shibuya; Yukio Takeshita; Makoto Kubo; Noriko Uesugi; Masafumi Yano (Case Reports in Rheumatology)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a type of antineutrophil cytoplasmic antibody-associated vasculitis. Patients often present with peripheral neuropathy and purpura, suggesting impairment of small vessels, especially capillaries. However, medium-sized vessels and small vessels with a vascular diameter larger than that of capillaries may also be impaired, causing atypical findings. We report a case of EGPA treated with corticosteroids, cyclophosphamide, and mepolizumab. Renal biopsy revealed vasculitis of the interlobular arteries as the cause of glomerulonephritis and interstitial nephritis. This case suggests the importance of considering vessels upstream of capillaries dominant EGPA as a differential diagnosis in patients with eosinophilia.